Waste from hazelnut cultivation as a potential feed source for farm animals - Gryszkiewicz-Zalega, Dorota; Horaczek, Tomasz; Borkowska, Anna I.; Yilmaz, Ferah; Küçükaydın, Selçuk; Klimek, Kamila E. (Journal of Water and Land Development, 2026)
The use of agricultural and food industry by-products as alternative feed sources is gaining importance in the context of global environmental and economic challenges. The leaves and husks of hazelnuts (Corylus avellana) are rich in crude fibre and microelements, which may make them suitable for use in livestock feed. The aim of the study was to analyse and compare the chemical composition and nutritional value of the leaves and husks of four hazelnut varieties (‘Kataloński’, ‘Olbrzymi z Hale’, ‘Olga’, ‘Webba Cenny’) in terms of their potential use as feed components. Significant differences between biomass types and varieties were found in most of the analysed parameters. The leaves were characterised by higher nitrogen (up to 1.11%), phosphorus (up to 0.109%), calcium (up to 1.042%) and magnesium (up to 0.264%) content, which indicates their potential as a protein-mineral supplement. The husks showed higher potassium (up to 2.037%), sodium, iron (up to 3032.9 mg∙kg−1), manganese and zinc, suggesting their potential use as a source of fibre and trace elements. Both the leaves and husks of hazelnuts are characterised by a diverse chemical composition, indicating their potential use in livestock nutrition, especially in regions with a deficit of traditional feed sources. Further research on the digestibility and effect of these components on animal health and production parameters is needed to determine the full range of their practical usefulness in sustainable nutrition.